2015
DOI: 10.5506/aphyspolbsupp.8.439
|View full text |Cite
|
Sign up to set email alerts
|

Quark Properties from the Hadron Resonance Gas

Abstract: We show how the quark free energy can be determined from a string and the Hadron Resonance Gas model with one heavy quark below the de-confinement phase transition. We discuss the interesting problem of identification of degrees of freedom at increasing temperatures, as well as the relevance of string breaking and avoided crossings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…This approach has been applied, for example, in the pure gauge theory to extract an effective glueball mass and spectrum based on the lattice results on pressure and trace anomaly [28,29]. For the case of QCD, the constraint imposed by the trace anomaly on the hadronic spectrum has been investigated [30,31]. In this work, we focus on the impact of recent LQCD data on the fluctuations of conserved charges.…”
Section: Equation Of State Of Hadronic Mattermentioning
confidence: 99%
“…This approach has been applied, for example, in the pure gauge theory to extract an effective glueball mass and spectrum based on the lattice results on pressure and trace anomaly [28,29]. For the case of QCD, the constraint imposed by the trace anomaly on the hadronic spectrum has been investigated [30,31]. In this work, we focus on the impact of recent LQCD data on the fluctuations of conserved charges.…”
Section: Equation Of State Of Hadronic Mattermentioning
confidence: 99%
“…This is unlike some weakly bound states, such as e.g. the deuteron, which average out within temperature intervals comparable to the binding energy [3]. The Hadron Resonance Gas (HRG) implements this idea as a multicomponent system of non-interacting pointlike hadrons which is expected to work below T c .…”
Section: The Hot Qcd Vacuum and The Hadronic Spectrum With Uds Quarksmentioning
confidence: 99%
“…. , Q N ) to the system, the Hamiltonian and its eigenvalues are modified, H → H + N i=1 V Q i , E n → E n +∆E n,Q , and there appears a volume independent shift of the thermodynamic quantities, In this contribution we review how these thermodynamic shifts provide information on heavy quark string breaking dynamics when a test heavy quark-antiquark pair separated at a fixed distance is placed in the hot QCD vacuum below the phase transition [2][3][4][5][6]. Note the these shifts are not true thermodynamic quantities.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of the so-called X,Y,Z states arises the question if these states must be included in the PDG and whether or not they add redundancy when building the hadron spectrum [4,6]. In this work we study this effect for the X(3872) resonance, a 1 ++ state discovered in 2003 by the Belle Collaboration [7], whose properties point to a dominant DD * -molecular structure.…”
mentioning
confidence: 98%
“…These authors concluded that certain interactions do not create new states but just reorder the already existing ones. For the deuteron, a J PC = 1 ++ np composite, the nearby np continuum compensates the weak binding effect and the overall contribution of the deuteron is zero as depicted in [6].…”
mentioning
confidence: 99%